2015
DOI: 10.1002/jmri.24983
|View full text |Cite
|
Sign up to set email alerts
|

Likert score 3 prostate lesions: Association between whole‐lesion ADC metrics and pathologic findings at MRI/ultrasound fusion targeted biopsy

Abstract: For score 3 lesions in patients without prior negative biopsy, whole-lesion ADC metrics help detect GS > 6 cancer while avoiding negative biopsies. However, deferral of fusion biopsy may be considered for score 3 lesions in patients with prior negative biopsy (without applying whole-lesion ADC metrics) given exceedingly low (∼ 2%) frequency of GS > 6 tumor in this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 37 publications
2
17
1
Order By: Relevance
“…Of these 16 lesions, 12% (2/16) were Gleason 4 + 3, and 6% (1/16) were GS: the remainder were GS 3 + 4. That study indicated that the prostate lesions evaluated on 3T multiparametric MRI as Likert score 3 were associated with a low likelihood of the presence of CSCa . In the current study, the positive rate of CSCa per patient was 83.0% (177/213) in Likert scores 4 and 5 versus 14.2% (7/49) in Likert score 3 ( P < 0.0001).…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Of these 16 lesions, 12% (2/16) were Gleason 4 + 3, and 6% (1/16) were GS: the remainder were GS 3 + 4. That study indicated that the prostate lesions evaluated on 3T multiparametric MRI as Likert score 3 were associated with a low likelihood of the presence of CSCa . In the current study, the positive rate of CSCa per patient was 83.0% (177/213) in Likert scores 4 and 5 versus 14.2% (7/49) in Likert score 3 ( P < 0.0001).…”
Section: Discussionsupporting
confidence: 48%
“…That study indicated that the prostate lesions evaluated on 3T multiparametric MRI as Likert score 3 were associated with a low likelihood of the presence of CSCa. 26 In the current study, the positive rate of CSCa per patient was 83.0% (177/213) in Likert scores 4 and 5 versus 14.2% (7/49) in Likert score 3 (P < 0.0001). We showed that Likert score 3 lesions were associated with a low percentage of CSCa using the technique of MRUS fusion TB.…”
Section: Discussionsupporting
confidence: 40%
“…This needs to be considered in the context of a "miss rate" of around 10% for a PIRADS score of 1-2. Importantly, detection rates have been shown to be higher in the peripheral zone [14] and as high as 40% in the context of a second-biopsy population [15], suggesting some PI-RADS 3 lesions deserve biopsy, whereas others could be safely deferred. Informing management of such lesions is particularly relevant given the reported prevalence of indeterminate of 20.5-26.3% using earlier Likert-based systems [10,[16][17][18] is predicted to increase with a switch to using the PI-RADS-version 2 reporting system [19].…”
Section: The Recently Updated Prostate Imaging-reporting and Data Sysmentioning
confidence: 99%
“…Their maximal AUC of 0.71 was lower than our present results and based on a single sequence analysis. Rosenkrantz et al applied different features of first order to discriminate lesions with Gleason >6 to others amongst VS lesions. Harbouring similar range of values to our present results, entropy of ADC alone failed to discriminate those even in their larger cohort.…”
Section: Discussionmentioning
confidence: 99%